Single-phase Na1.0TiO2: Solid-state synthesis and characterisation by high-resolution powder diffraction - Clarke, S; Duggan, A; Fowkes, A; Harrison, A; Ibberson, R; Rosseinsky, M (1996)
We report previously unsuspected multiple-phase behaviour in the NaxTiO2 (x ≈ 1) system and a technique for the preparation of single-phase Na1.0TiO2: very high resolution powder diffraction data are needed for effective characterisation.